Uncertain productivity growth and the choice between FDI and export - Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2009)
The underlying model analyzes the first time foreign market entry decision of a representative investor who can choose between export and FDI. The model combines the proximity-concentration trade-off framework with the real option methodology and sheds light on the effects of productivity growth. On the basis of a Geometric Brownian motion, three different productivity scenarios are considered (no growth, deterministic growth, uncertain growth) and opposed to each other. The introduction of productivity growth increases the likeliness of first time market entry through FDI. If the firm is confronted with uncertain productivity growth, market entry through FDI increases even further. Uncertainty is identified as a compounding force for the derived growth effects. The findings contribute to the static general equilibrium models which neglect intertemporal selection effects.
Keywords: F17; F21; F23; 330; export; FDI; uncertain productivity growth; real option approach; Internationale Markteintrittsstrategie; Direktinvestition; Export; Realoption; Produktivität; Unternehmensentwicklung; Theorie